Amor en femenino: resignificación del concepto de amor como posibilidad de transformación social - Muñoz Rodríguez, Ivonne (Universidad Michoacana de San Nicolás de Hidalgo, 2023)
The present investigation is a philosophical reflection concerning a dialogue between love and feminista thought. The objective of resignifying the concept of love is to propose an Eros in the political dimension that permits the possibility of a social transformation. This concern is sustained by the problem of the systematic violence that shapes the reality of the world we inhabit and that, to a large extent, its ravages degrade life, the relationships between human beings, and the relationship between human beings and all living things. Love under the look of Hannah Arendt, Simone Weil, and María Zambrano reveals a powerful and transformative force that coincides with the stand of some of the philosophers of the tradition mentioned in this work. The relationship between the three philosophers mentioned above and the feminist philosophers who share their thoughts propose love as the force capable of safeguarding life in this world and as something totally different from the subjective experience that, from the patriarchal logic, is known as love. Love in feminine is a representation of the multiple ways of situating love in human existence, which until now is in the process of discovery to reach that process of transformation and reconciliation with the world.

La presente investigación es una reflexión filosófica sobre el amor en diálogo con el pensamiento feminista. El objetivo de resignificar el concepto de amor es plantear un Eros en la dimensión política que permita la posibilidad de una transformación social. Esta inquietud se sostiene a partir del problema de la violencia sistemática que configura la realidad del mundo que habitamos y que en gran medida sus estragos degradan la vida, las relaciones entre los seres humanos y la relación del ser humano con todo lo viviente. El amor desde la mirada de Hannah Arendt, Simone Weil y María Zambrano, revela una potencia creativa y transformadora que coincide con la postura de algunos filósofos de la tradición mencionados en este trabajo. La relación entre estas tres filósofas y las filósofas feministas que comparten su pensamiento proponen el amor como la fuerza capaz de salvaguardar la vida en este mundo y como algo totalmente diferente a la experiencia subjetiva que desde la lógica patriarcal se conoce como amor. El amor en femenino es una representación de las múltiples formas de situar el amor en la existencia humana, que hasta el momento está en vías de su descubrimiento para llegar a ese proceso de transformación y de reconciliación con el mundo.
Instituto de Investigaciones Filosóficas. Facultad de Filosofía. Doctorado Institucional en Filosofía
Keywords: info:eu-repo/classification/cti/4; IIF-D-2023-1145; Realidad; Transformación; Feminismo; http://bibliotecavirtual.dgb.umich.mx:8083/xmlui/handle/DGB_UMICH/16579